Up-and-coming anti-epileptic effect of aloesone in Aloe vera: Evidenced by integrating network pharmacological analysis, in vitro, and in vivo models - Wang, Yan; Li, Chang; Xiong, Zhongyv; Chen, Niangen; Wang, Xuesong; Xu, Junyv; Wang, Yuemei; Liu, Longfeng; Wu, Hang; Huang, Caihui; Huang, Aiqin; Tan, Jiajia; et al. (Frontiers in Pharmacology, 2022)
Background: Aloe vera is a medically valuable plant with anti-epileptic activity; however, its mechanism of action remains unknown. In this study, network pharmacological, in vitro, and in vivo experiments were carried out to explore the potential anti-epileptic components and targets of Aloe vera. Methods: The main active components of Aloe vera were identified by searching the Traditional Chinese Medicine System Pharmacology Database. Targets of Aloe vera were predicted using SwissTargetPrediction, whereas information about the epilepsy disease targets was obtained from Gene Cards. The protein–protein interaction network and core targets were screened according to the topological structure and CytoNCA plugin. The glutamate-induced HT22 cell line and pentylenetetrazol-induced seizure rats were used to confirm the effect of aloesone by detecting reactive oxygen species (ROS) and apoptosis, and predicting the targets. Results: A total of 14 core active components were selected based on the screening criteria of oral bioavailability ≥ 30% and drug-likeness ≥ 0.10. Four compounds, namely linoleic acid, aloesone, isoeleutherol glucosiden qt, and anthranol, demonstrated the potential ability of crossing the blood-brain barrier. A total of 153 targets associated with epilepsy were predicted for the four compounds. Moreover, after network analysis with CytoNCA, 10 targets, namely, MAPK1, SRC, MARK3, EGFR, ESR1, PTGS2, PTPN11, JAK2, PPKCA, and FYN, were selected as the core genes, and SRC, which has been predicted to be the target of aloesone and anthranol, exhibited the highest subgraph centrality value. In vitro experiments confirmed that aloesone treatment significantly inhibited the glutamate-induced neuronal injury by reducing the intracellular ROS content and the early phase of apoptosis. Additionally, treatment with 50 mg/kg aloesone resulted in anti-seizure effects by reducing the seizure score and prolonging the latent period in acute and chronic rats. Furthermore, aloesone treatment increased the phosphorylation of c-SRC at Y418 and reduced the phosphorylation at Y529, simultaneously activating c-SRC. Conclusion: Integrating network pharmacology with in vitro and in vivo experiments demonstrated that aloesone, which inhibited seizure by activating c-SRC, is a potential anti-seizure compound present in Aloe vera.